2007
DOI: 10.2175/106143007x183763
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Disinfection Alternatives: Chlorine, Ozone, Peracetic Acid, and UV Light

Abstract: Disinfection tests were carried out at pilot scale to compare the disinfection efficiency of ozone, sodium hypochlorite (NaOCl), peracetic acid (PAA), and UV irradiation. Total coliforms, fecal coliforms, and Escherichia coli were monitored as reference microorganisms. Total heterotrophic bacteria (THB) were also enumerated by cytometry. At similar doses, NaOCl was more effective than PAA, and its action was less affected by contact time. The results obtained by ozonation were comparable for total coliforms, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 10 publications
2
34
0
3
Order By: Relevance
“…This indicates that the traditional C•t (dose amount x contact time) concept may need a weighting coefficient for the t term. Additionally, PAA seems to possess faster inactivation kinetics for E. coli compared to total coliform bacteria (TCB), which was also confirmed by Mezzanotte et al (2007) …”
Section: Introductionmentioning
confidence: 65%
“…This indicates that the traditional C•t (dose amount x contact time) concept may need a weighting coefficient for the t term. Additionally, PAA seems to possess faster inactivation kinetics for E. coli compared to total coliform bacteria (TCB), which was also confirmed by Mezzanotte et al (2007) …”
Section: Introductionmentioning
confidence: 65%
“…For example, Francy et al [38] reported that because of significant removal by MBR, ultraviolet disinfection after MBR treatment provided little additional log removal of any organism except for somatic coliphage (>2.18), whereas ultraviolet or chlorine disinfection after CAS treatment provided significant log removals (above the analytical variability) of all bacterial indicators (1.18-3.89) and somatic and F-specific coliphage (0.71 and >2.98). In another study, the chlorine required to remove 100% of fecal coliform from MBR effluent was 2.9 mg/L, less than for the sand filtration process that required 8 mg/L, and less than the typical dose of 5-20 mg/L, although some viruses have been known to survive disinfection in low doses [52,117,118]. The study by Natvik et al [119] suggested a minimal requirement for post-MBR disinfection, which can be achieved using a reduced ultraviolet irradiation.…”
Section: Requirement Of Post-disinfectionmentioning
confidence: 99%
“…Ozone is an extremely reactive oxidizing agent characterized by disinfection efficiencies higher than the disinfection with chlorine [18]. The bactericidal power is generally attributed to the ability to destroy the cell wall of the microorganisms.…”
Section: Action Mechanismsmentioning
confidence: 99%